Gas analysis system for studying sand mold’s atmosphere during steel casting - Jakub Wielgosz; Alexis Vaucheret; Philippe Jacquet; Jean-François Carton (MethodsX, 2025)
The composition of the mold atmosphere plays a critical role in mold-metal interactions during steel casting and is a root cause of certain casting defects. However, studying this atmosphere is challenging due to technical difficulties in extracting gases from sand molds and the harsh conditions of the metal casting process. Most of the studies realized in the field uses gas chromatography and mass spectrometry technics to investigate atmosphere in a foundry mold. Single-gas sensors, being readily available nowadays, present a cost-effective alternative to aforementioned technics. In this paper, we present an innovative gas analysis system designed for real-time, in-situ monitoring of the mold atmosphere. This system has been developed in collaboration between ENSAM Cluny (LaBoMaP) and the industrial partner Safe Metal. • The paper presents the design, fabrication, operation and validation of an in-house foundry gas analyzer. • Issues regarding gas sampling from a sand mold are discussed. • The measurements with the analyzer were confronted with a reference gas mixture as well as with the foundry gas samples analyzed by µGC method.